Confounding giant right atrial mass - Sefa Tatar; Ahmet Taha Sahin; Mehmet Işık; Niyazi Görmüş (The Egyptian Heart Journal, 2024)
Abstract Background Primary cardiac tumors are uncommon, with approximately 70–80% classified as benign. Myxomas constitute roughly half of all benign cardiac tumors, while cardiac hydatid cysts are exceptionally rare. Shortness of breath is a prominent symptom associated with these conditions. Echocardiography serves as the primary diagnostic tool, enabling early detection. The preferred course of action involves the surgical excision of the mass. Case presentation Our first case, a 51-year-old female presented to the cardiology outpatient clinic with complaints of shortness of breath and palpitations persisting for 3 months. Physical examination and tests were within normal limits. Echocardiography revealed a right atrial myxoma measuring 65 * 35 mm. Despite not affecting valve and ventricular functions, the mass was surgically resected. Our second case, a 55-year-old male admitted to the cardiology clinic with recurrent fever, shortness of breath, and chest pain. Physical examination and tests were normal. Echocardiography revealed an echogenic mass with a septate appearance adhering to the free wall of the right atrium. The patient, diagnosed with a hydatid cyst, underwent surgical resection. Conclusions We came across two different cases of RA masses which happened to be myxoma and hydatid cysts, and we managed accordingly. The right atrial myxomas typically present with nonspecific shortness of breath unless they cause valve obstruction. In cases where clinical findings suggest infection in the right atrial masses, it is essential to consider hydatid cyst as a potential diagnosis alongside the initial consideration of vegetation.